The Influence of Macroeconomic Fundamentals, Decisions Investment, And Capital on Stock Returns with Risk Profile and Earning as Intervening Variables and Good Corporate Governance as a Variable Moderation (Study of Banking Companies in Indonesia) - Wijaya, Andjar Eka; Ratnawati, Tri; Pristiana, Ulfi (International Journal of Economics (IJEC), 2025)
This study aims to analyze the influence of macroeconomic indicators, investment decisions, capital, risk profile, earnings, and corporate governance on stock returns in banking companies in Indonesia using the SEM-PLS method. The research results show that macroeconomic indicators (inflation, exchange rate, and interest rate) do not significantly affect stock returns either through risk profile or earnings. But if the macroeconomic variables are tested without mediation variables and directly on stock returns, they have a significant impact.In addition, investment decision indicators (current asset ratio and total asset growth), capital indicators (capital adequacy ratio and debt equity ratio), as well as risk profile indicators (non-performing loan and loan deposit ratio) also do not have a significant impact on stock returns. Similarly, the earning indicators (ROA, ROE, and NIM) and good corporate governance (board of directors and number of commissioners) do not show a significant influence on stock returns. These findings indicate that external factors and other variables are more dominant in influencing stock returns in banking companies in Indonesia.